Diffusion-weighted magnetic resonance imaging with echo-planar and non-echo-planar (PROPELLER) techniques in the clinical evaluation of cholesteatoma - María Dolores Moreno-Ramos; Miguel Olivencia Pérez; Juan Antonio Ibáñez Rodríguez; Mª José Gómez Galán; Francisco Javier Ramos Medrano (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Background: Diffusion-weighted magnetic resonance imaging (DWI) is an alternative to second-look surgery for the detection of cholesteatoma. Purpose: To assess the utility of DWI with echo-planar (EPI-DWI) and non-echo-planar (PROPELLER) sequences for the diagnosis of primary and recurrent cholesteatoma.  Materials and methods: A prospective study of 33 ears, 21 with previous cholesteatoma surgery. Twelve patients were asymptomatic, with 4 showing signs suggestive of cholesteatoma in previous CT scans. The MRI protocol was: axial and coronal T1-weighted and T2-weighted imaging, and diffusion-weighted sequences by both EPI-DWI and PROPELLER techniques. The results were correlated with the clinical examination and subsequent surgical findings. Ten patients undergoing ear surgery for other reasons were included as negative controls. Results: The diagnostic accuracy was calculated with the 22 patients who underwent surgery and the negative controls. Both diffusion-weighted sequences showed a specificity of 100%. The sensitivity of PROPELLER was 95%, compared to 20% for EPI-DWI. The latter showed non-specific imaging with bone artefacts, thus making impossible to confirm or exclude the diagnosis. The PROPELLER technique yielded one false negative, compared with 16 by EPI-DWI. Both techniques gave a false negative in one case of a primary cholesteatoma. A positive result was obtained in two patients with no clinical suspicion of recurrence.  Conclusions: In contrast to EPI-DWI, PROPELLER is a reliable technique for diagnosing cholesteatoma. As positive results were found in asymptomatic patients, we recommend regular monitoring by PROPELLER, even in the absence of clinical findings.